Studies on judo technique, with special reference to Kamae and Kuzushi - Asami, T.; Matsumoto, Y.; Kawamura, T. (Association for the Scientific Studies on Judo, Kodokan, 1972)
There are two forms of Kamae (posture) in Judo, viz., the Shizentai (natural posture) and the Jigotai (defensive posture). Generally speaking, the Shizentai is considered to be the Kamae for attack and the Jigotai the Kamae for defence. This paper deals with the investigations into the problems of: which Kamae is actually more resistant to the forward Kuzushi, or what difference is there in the muscular activity of the legs depending on the form of Kamae, or what is the effect of the different forms of Jigotai on the defensive strength against forward and backward Kuzushi (unbalancing the opponent) or against right and left Kuzushi?